Cultural stress, family functioning, hazardous alcohol use, and mental health among Latin American parents in the United States: A latent profile analysis - Andrea Lopez-Soto; Esmeralda Ramírez; Duyen H. Vo; Aigerim Alpysbekova; Seo Woo Lee; Maria Duque; Lawrence Watkins; Cory L. Cobb; Beyhan Ertanir; Alejandra Garcia Isaza; Evelyn Gualdron; Sumeyra Sahbaz; et al. (PLoS ONE, 2025)
There is a limited understanding of how different subgroups of Latin American immigrant parents experience cultural stressors, as well as its impact on family dynamics, health behaviors, and mental health. The present study aimed to (1) identify latent cultural stress profiles among Latin American immigrant parents in the U.S. and (2) examine differences among these profiles concerning family intimacy, democratic parenting style, family conflict, hazardous alcohol use, and depressive and anxiety symptoms. Participants consisted of a sample of 1,351 parents (61.9% female; M age = 39.83, 62% first-generation; North America [61%], Central America and the Caribbean [21%], and South America [19%]) of children aged 8–16. We used latent profile analysis to identify subgroups of cultural stress, defined by perceived discrimination (PDS) and negative context of reception (NCR). Multinomial logistic regression was conducted to examine key correlates of profile membership. Five latent profiles were identified (1) Low PDS/NCR (22.2%), (2) Low PDS/Elevated NCR (14.8%), (3) Moderate PDS/NCR (18.7%), (4) Elevated PDS/NCR (33.5%), and (5) Highest PDS/NCR (10.8%). Compared with Profile 1 (Low PDS/NCR), parents in Profiles 2–5 generally reported lower family intimacy (RRR = 0.93–0.97). Parents in Profile 5 (Highest PDS/NCR) reported more family conflict (RRR = 1.13), hazardous alcohol use (RRR = 1.20), depressive symptoms (RRR = 1.31), and anxiety symptoms (RRR = 1.29), with markedly elevated depressive (RRR = 22.94) and anxiety symptomatology (RRR = 17.48) compared with Profile 1. Our findings suggest the presence of vulnerable subgroups due to cultural stress among Latin American parents in the United States. A better understanding of cultural stress patterns may improve current and future interventions tailored for Latin American families, addressing health disparities within this population.